ECONOMIC VALUATION OF THE DIRECT BENEFITS OF CAPTURE FISHERIES AND THE CONTRIBUTION OF MANGROVES FOR FISHERMEN OF BATU ITAM VILLAGE, BELITUNG - Yolanda, Yolanda; Umroh, Umroh; Wahidin, La Ode (Jurnal Perikanan Unram, 2025)
The coastal area of Batu Itam Village possesses significant potential in natural resources and environmental services, along with a high level of biodiversity. This study aims to determine the direct economic benefits of capture fisheries within the mangrove ecosystem and assess the contribution of these direct economic values to household incomes in Batu Itam Village. The research employs a quantitative descriptive methodology and was conducted in June 2024. Respondents were selected using snowball sampling and census methods. The study involved two groups: 27 mangrove fishermen identified through a census approach and 20 general fishermen selected using the Slovin formula. Primary data were collected via respondent interviews, while secondary data were obtained through literature reviews. Mangrove area measurements were conducted spatially using Sentinel-2A satellite data. The findings reveal that the direct economic value of the mangrove ecosystem in Batu Itam Village amounts to IDR 1,376,670,000 per year, with an average of IDR 275,334,000 annually. This value is supported by the mangrove ecosystem’s area of 205.13 hectares. Among the resources, fish provide the highest direct economic benefit compared to squid, crabs, shrimp, and shellfish. The contribution of income derived from the mangrove ecosystem constitutes 74% of the total household income for fishermen in Batu Itam Village